Liability of domain name registries: Don't shoot the messenger. Issue 2 (April 2016) - Truyens, M.; Van Eecke, P.
Abstract: The domain name system (DNS) is fundamental to the Internet, because it translates domain names to and from computer (IP) addresses. This system is, however, increasingly used as a tool to combat unwanted online content. In this process, the system's most central operators ("registries") are targeted by right holders, authorities and other claimants, even though the registries fulfil a mere technical role as an online intermediary, and are quite distanced from the actual content. This contribution presents arguments why registries and other DNS-operators would be protected against several types of domain blocks, monitoring duties and liability claims. These arguments are not only supported by a forward-looking interpretation of the special protection regime for mere conduit, caching and hosting providers of the EU eCommerce Directive 2000/31/EC, but also by Enforcement Directive 2004/48/EC and general EU law, as interpreted by the Court of Justice of the European Union.